REPRESENTATION OF SOCIAL ACTORS IN REPUBLIKA.CO.ID AFTER INAUGURATION OF MOCHAMAD IRIAWAN AS ACTING OF WEST JAVA GOVERNOR, INDONESIA - Bernadus Wahyudi Joko Santoso; Mohamad Yusuf Ahmad Hasyim; Maria Johana Ari Widayanti; Eko Widianto (Linguistik Indonesia, 2022)
The purpose of this study is to investigate social actors' representation on the inauguration of Acting Governor in West Java 2018, from Ahmad Heryawan (Aher), representing the Right Islamic Party, to Commissioner General Mochamad Iriawan (Iwan), representing the Nationalist Party, in the perspective of Critical Discourse Analysis (CDA) Theo van Leeuwen model (2008). Method of data collection were the method of reading, namely the intensive and comprehensive reading. We read the social actor’s representations that were represented in mass media online: Republika.co.id during 3 days of news, on 18, 19, and 20 of June 2018 where there was a lot of polemics over the Irawan’s inauguration. The Republika.co.id was more inclined than supported the inauguration, though according to Indonesian Government, it was legal because in that moment Irawan was as Main Secretary of the National Resilience Institute (Lemhannas), not as an active Chief of Police in Special Capital Region, Jakarta. The data were obtained by copying-paste technique. The analytical methods used were descriptions, interpretations, and explanations. The results of the analysis showed that all pro-government social actors, both in government and "outside the government", supported Irawan's inauguration as acting governor of West Java. On the other hand, social actors who did not support the inauguration are reported as social actors who obey the constitution, educate the people, encourage honesty, uphold democracy and so on. That was why, Irawan's inauguration as acting governor in West Java was reported negatively, such as unconstitutional inauguration, fooling people, violating democracy, public deception, and so on. The difference of the social actors’ representation above was undeniable due to differences in the ideology (nationalism versus Islamism) and political interest ahead of the presidential election last year, in 2019. Thus, it proves that the study of CDA perspective can show us the relationship between language use (discourse), ideology, ‘hidden’ power and also discourse and social practice.